LEARNING TO WRITE NEWS BY DEVELOPING A MEDIA E-LEARNING BY MOODLE-BASED - Mahpudoh Mahpudoh; Rina Andriani; Diana Romdhoningsih; Lutfiyah Lutfiyah; Irma Nurmala Dewi (Sean Institute, 2023)
One of the fundamental journalistic skills required of students, particularly in the Indonesian Education and Literature Study Program, is the ability to write news that produces events that are directly experienced and observed in social reality. This research is a developmental one, and its goal is to make Moodle-based E-Learning media for learning to write news with tools like PowerPoint software, Google Slides, and moodle. This research is being conducted in the United Kingdom. The research and development method and the define, design, development, and dissemination (4D) development model are being utilized in this study. The data was gathered using a non-test instrument in the form of a questionnaire distributed to two media experts and two material experts. Data analysis techniques used include validation analysis by experts using a Likert Scale. The results of the research are in the form of the feasibility of learning media products totaling three learning materials using a Likert scale with a score of 1-5 as follows: a) Media experts obtain a score of 82.31% from the validation results and are included in the very feasible category; b) Material experts get a score of 78.09% from the validation results and are included in the appropriate category. Based on the feasibility findings, it has been determined that Moodle-based E-Learning media is appropriate for news writing learning courses.